SERVICE QUALITY DIMENSIONS, PERCEIVE VALUE AND CUSTOMER SATISFACTION: ABC RELATIONSHIP MODEL TESTING - Yeop Yunus, Nek Kamal; Ismail, Azman; Ranee Juga, Zubrina; Ishak, Salomawati (International Business Education Journal, 2009)
The study was conducted to examine the effect of service quality and perceived value on customer satisfaction using a sample of 150 usable questionnaires gathered from undergraduate students in one public university in Sarawak, Malaysia. The outcomes of hierarchical regression analysis showed four important findings: firstly, relationship between perceive value and reliability significantly correlated with customer satisfaction. Secondly, relationship between perceive value and responsiveness significantly correlated with customer satisfaction. Thirdly, relationship between perceive value and assurance significantly correlated with customer satisfaction. Fourthly, relationship between perceive value and empathy significantly correlated with customer satisfaction. This result confirms that perceive value does act as partial mediating variable in the service quality models of organizational sample. In addition, implications and limitations, as well as directions for future research are elaborated.